Islamic Psychotherapy for Children and Adolescents - Muhamad Afifudin Alfarisi (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2019)
The two great paradigms typically seen as two opposing are Islam and Psychology, which accumulate the cultural paradigm associated with mental health. Depending on the history, personality inside Islam and psychopathology has been present for centuries. Nowadays, Indonesia well-known as a great Muslim population, which means, the need for mental health service among Muslim society is paramount. Arising awareness of mental health issues and services has increased in the use of mental health services. Therefore, it is substantial that the psychological society at richly understand how Islamic principles can be integrated into psychotherapy. This observation tries to outlining strategies to incorporate the Islamic values into psychotherapy with adults, which the research concerning utilizing Islamic psychology principles with children and adolescents not properly utilizing.